Theoretical framework of fair distribution of affordable housing in China - Zhang, Tao; Hashim, Ahmad Hariza (Canadian Center of Science and Education, 2011)
Urbanization and industrialization in China result in dramatic growth of population in urban areas. The housing price rises so high that low-income people living in urban cannot afford to buy their own houses. In order to alleviate their housing plight, affordable housing has been built in mainland China. However, unfair distribution of affordable housing failed to accomplish the goal of this program. The paper firstly introduces the current situation and problem of affordable housing distribution. It then discusses the rationale of Theory of Justice from John Rawl, and puts forward a systematic legal framework, which consists of affordable housing legislation, enforcement, judiciary and sanction, to safeguard the justice of affordable housing distribution.